Morbus Hansen Multibacillary Type Mid Borderline: A Case Report - Irene Ardiani Pramudya Wardhani; Winda Wijayanti; Dina Febriani; Nurrachmat Mulianto (HM Publisher, 2022)
Background: Morbus Hansen (MH) is a granulomatous infectious disease caused by an obligate intracellular pathogenic bacterium, Mycobacterium leprae (M. leprae). Cardinal signs of Hansen's morbus (MH) include patches of numb skin, thickening of the peripheral nerves, and acid-fast bacteria (AFB) on a skin smear or biopsy. This case report aims to establish the diagnosis of mid borderline (BB) MH with clinical and histopathological examination. Case presentation: A 44-year-old woman presented with red patches on her face and body 1 month ago. Madarosis and multiple erythematous plaques confluent, poorly demarcated, raised edges, atrophic center with some smooth shiny and some rough surfaces found in the facial region and superior extremities et al. bilateral inferior with bilateral auricular infiltrates. A sensory examination of the lesion showed decreased sensitivity to pain and temperature. Skin-slit smear examination showed AFB with bacterial index (IB) +2 and morphological index (IM) 30%. On histopathological examination with hematoxylin and eosin staining, Grenz zone appeared, epithelioid granuloma affecting the epidermis, no lymphocytes, and no giant Langhans cells were found, and nerves were surrounded by lymphocytes and granulomas. On fite-faraco staining, BTA was obtained with IB +3 and IM 30%. The diagnosis of MH type BB was established, and the patient was given multidrug therapy (MDT) multibacillary (MB). Conclusion: Morbus Hansen type BB has a typical histopathological picture of granulomas composed of mature epithelioid cells, Grenz zone, AFB, enlarged and swollen nerves surrounded by lymphocytes or infiltrated with granulomas without damage. After 3 months of therapy, there was a decrease in IB and IM on AFB examination.